Association between sociodemographic status and pulmonary tuberculosis: a case control study - Ratta, Amandeep Kaur; Kubde, Sanjay S.; Patle, Rupali (International Journal Of Community Medicine And Public Health, 2018)
Background: The case control study, an analytical approach of epidemiology is a very important tool to detect the strength of association of risk factors with a disease. The objective of the study was to evaluate association between sociodemographic profile and pulmonary tuberculosis. Methods: This was case control study carried out in tertiary care hospital and urban field practice area from July 2010 to November 2012. Total 150 cases, 150 hospital control and 150 community controls were included in the study according to predefined inclusion and exclusion criteria. The study participants were interviewed and examined according to the preformed and pretested proforma in the respective OPDs. Results: Mean age of cases was found to be 35.94 years and those of hospital controls and community controls were 36.12 and 36.08 years respectively. Maximum cases and controls were Hindu, married, from urban area and belongs to upper lower socioeconomic class. Low socioeconomic status was found to be associated with risk of pulmonary tuberculosis and this association was statistically significant (OR=4.45, 95% CI 2.53–7.82, p<0.0001). Conclusions: Low socioeconomic status showed significant association with pulmonary TB with both the control groups.